Narrative arcs and shaping influences in long-term medication adherence. (September 2021) - Nakata, Cheryl; Sharp, Lisa K.; Spanjol, Jelena; Cui, Anna Shaojie; Izberk-Bilgin, Elif; Crawford, Stephanie Y.; Xiao, Yazhen
Abstract: Long-term adherence to medications is not well understood and poses a significant challenge for many chronically ill persons. Past research provides insights on adherence in short durations such as a day or several weeks, even though chronically ill patients are required to take medications for periods as long as a lifetime. To fill this important knowledge gap, we study the temporal unfolding of prolonged medication-taking experiences among thirty adults, mostly African American, with chronic hypertension in the U.S. Specifically, we take an extended, experience-centered, narrative approach to examine retrospective patient accounts of adherence efforts over spans of one year to more than four decades. Applying Gergen and Gergen's concept of narrative forms (1983), we find four distinct narrative arcs, or patterned sequences of medication consumption, that we term Out of the Gate, Existential Turn, Fits and Starts, and Slow Climb, along with individual and social elements that shape and shift practices in the context of time. Highlights: Long-term adherence to medications varies among chronically ill patients. Patient narratives reveal extended adherence efforts follow four patterns or arcs. Over the years, adherence rises, falls, and remains stable in distinct phases. Individual and social factors spur, stop, form, and alter movements between phases. Adherence temporally unfolds in subtle ways, unlike the standard medical depiction.